The Construction of and Order: Structural Adjustment in Costa Rica 1985-1995 - Raventós Vorst, Ciska (1995)
This dissertation studies the political process of adjustment policies 1980-1995 in Costa Rica. Costa Rica, like most other Latin American countries, went through one of its worst economic crises during the early 1980's, a crisis that involved the state-centered ¨model¨ of inward-oriented import substitution industrilization O' Donnell, 1992; González Casanova, 1992.) Tho overcome this crisis, Costa Rica has followed stabilization policies proposed by the international Monetari Fund since 1980, and structural adjustment programas created and promoted by the World Bank since 1985.